Nurses and midwives' experience in providing fertility awareness-based methods, including natural family planning methods in Rwanda - Pauline Uwajeneza; Marilyn Evans; Pamela Meharry; Donatilla Mukamana; Yolanda Babenko-Mould; Patrick Munezero; Agnes Mukabaramba Kanimba (Elsevier, 2023)
Access to effective and acceptable family planning services in developing countries is an essential reproductive health intervention to reduce maternal deaths and prevent unwanted pregnancies. The purpose of this qualitative descriptive study was to gain an in-depth understanding of nurses' and midwives' experiences in providing information related to fertility awareness-based methods, including natural family planning, to clients in Rwanda. Face-to-face individual interviews were conducted with ten nurses and midwives who provide family planning services at six health centers in the Kicukiro district in Rwanda. The interviews were audio-recorded, transcribed verbatim into Kinyarwanda and then translated into English. Inductive content analysis was used for data analysis. Three themes were identified: 1) Fertility Awareness-Based Methods, including Natural Family Planning Method Facilitators and Barriers, 2) Advantages of Fertility Awareness-Based Methods, including Natural Family Planning Methods; and 3) Nurses' and Midwives' Attitude and Teaching of Fertility Awareness-Based Methods, including Natural Family Planning Methods. Study findings suggest that limited pre-service education and lack of in-service training about family planning contributes to nurses' and midwives' limited knowledge of Fertility Awareness-Based Methods, including Natural Family Planning Methods, and impacts their attitudes and skill level toward counselling clients. Nursing and midwifery schools need to improve how they teach Fertility Awareness-Based Methods, including Natural Family Planning, and health centers need to provide ongoing extensive in-service education to healthcare providers. There is a need to increase content related to family planning in nursing and midwifery education. These findings may also pertain to other developing countries like Rwanda and guide a positive change in family planning education for healthcare providers and FP services delivery.